Pengaruh ROA, DER, TATO, Dan ITO Terhadap Financial Distress Emiten Transportasi - Zaenal Arifin; Devyanthi Syarif; Ridwan (CV. ITTC INDONESIA, 2026)
Transportation firms operate with substantial fixed assets, volatile demand, and heterogeneous inventory structures. This study examines the effect of return on assets (ROA), debt to equity ratio (DER), total asset turnover (TATO), and inventory turnover (ITO) on financial distress measured by the continuous Springate S-Score. The sample comprises seven transportation issuers listed on the Indonesia Stock Exchange and 63 firm-year observations from 2017 to 2025. Audited annual reports and financial statements were traced to a source ledger before the ratios were calculated. Panel-model specification tests support pooled ordinary least squares, while conventional, HC3, and issuer-clustered standard errors are reported to assess inferential robustness. The model is statistically significant (F = 23.5726; p < 0.001), with an adjusted R-squared of 0.5929. ROA has a positive and significant effect on the S-Score, whereas DER, TATO, and ITO are not significant at the 5% level. Forty-seven observations (74.60%) fall below the descriptive distress threshold. The findings indicate that profitability represents the most consistent financial indicator in explaining transportation companies’ financial health. However, the interpretation should consider the mechanical overlap between ROA, TATO, and the Springate formula components. The study provides implications for managers, investors, and creditors in evaluating financial sustainability through integrated financial ratio analysis.